Evalution of stability of some titanium implant in various simulated biological fluids - (:unkn) unknown (CHIMINFORM DATA S A, 2006)
This paper studied the corrosion behavior of Ti/TiO2/P2O5-CaO-SiO2/physiological fluid interface by electrochemical methods. The bioactivity and surface structural changes of bioglass, 45S5 containing 45% SiO2, P2O5, 24.5% CaO and 24.5% Na2O all in weight percent, which was in plasma sprayed on titanium with 60Al(2)O(3)TiO(2) as a bond coating, were analyzed with complementary methods. In-vitro substrate assessment of bio-activity was carried out by immersion into biofluid. Fourier transform infrared spectroscopy (FTIR) and UV-VIS absorption spectroscopy was used to analyze the inorganic carbonate apatite layer formation on coating in an in vitro environment. Scanning electron microscopy (ESEM) was the tool for surface characterization.
Keywords: bioglass; apatite; biofluid; implant; IN-VITRO; CORROSION; BEHAVIOR